Chemical Composition of Citrus limon L. Burmf Peel Essential Oil from North East India. Issue 2 (3rd March 2020) - Paw, Manabi; Begum, Twahira; Gogoi, Roktim; Pandey, Sudin Kumar; Lal, Mohan
Abstract: Citrus limon L. Burmf (commonly known as lemon) is a small thorn bearing tree which belongs to the family Rutaceae cultivated in the tropical and subtropical regions of the world and mostly cultivated in North Eastern region of India. It bears many medicinal properties and used in the cosmetics industries and pharmaceutical industries. Apart from the plant, extracted peel essential oil of C. limon has many medicinal properties so it can be used in the treatment of different diseases. Essential oil was extracted using hydrodistillation and analyzed by using Gas chromatography/mass spectroscopy (GC/MS). A total of forty three compounds were identified of which limonene (55.40 %) and neral (10.39 %) were found as major compound followed by trans -verbenol (6.43 %) and decanal (3.25 %). The other compounds present were ethyl cinnamate (2.21 %), ethyl p-methoxycinnamate (2.21 %), cis -α-bergamotene (1.60 %), geraniol (1.48 %), trans -carveol (1.33 %), nonanal (1.19 %), linalool (1.16 %), α-terpineol (1.07 %), p-mentha-2, 8-dien-1-ol (0.90 %), estragole (0.73 %), α-fenchene (0.46 %), perillol (0.46 %), β-curcumene (0.45 %), trans -d-limonene oxide (0.43 %), 1-naphthalenamine (0.42 %), camphor (0.34 %), 3-carene (0.34 %), β-santalene (0.27 %), β-sesquiphellandrene (0.25 %), α-pinene (0.17 %), terpinen-4-ol (0.17 %), 3-terpinolenone (0.17 %), zizaene (0.16 %), germacrene -D (0.16 %), α-bisabolol (0.16 %), β-bisabolol (0.14 %), methyl n-hexadecanoate (0.14 %), citronellal (0.12 %), o-cymene (0.12 %), 1-undecanol (0.11 %) and sabinol (0.11 %) were identified as in minor quantities. Limonene was the major chemical compound in the C. limon peel essential oil which possess many medicinal properties could be used as a pharmaceutical industries.